Advancements in Healthcare through Design and Development of an Intelligent Intravenous Bag Monitoring and Alert System - Bin Ab Ghani, Mohd Khairul Akli; Rahim, Mohd Zain Bin Abdul; Azli, Muhammad Hanis Bin Mohd Khairul (Engineering And Technology Journal, 2023)
The Intelligent Intravenous Bag Monitoring and Alert System is a device designed for nighttime patient monitoring, allowing nurses to focus on other duties and prevent air bubbles from entering the patient's bloodstream. The device uses an S-type load cell to measure IV bag contents, and the Blynk app to display readings on a smartphone. The device's CPU, a NodeMCU, operates on a voltage range of 5V to 12V. The device's goal is to monitor the current IV content level, which can be checked using a smartphone and the LCD display. This innovative solution is particularly useful for intravenous (IV) treatment, which allows patients to receive fluids, medications, and nutrients directly into their veins. The device's effectiveness is further enhanced by the Blynk app.